D2 Receptors and Sodium Ion Channel Blockades of the Basolateral Amygdala Attenuate Lithium Chloride-Induced Conditioned Taste Aversion Applying to Cancer Chemotherapy Nausea and Vomiting - Zhi-Yue Gao; Chung Ming Huang; Cai-N Cheng; Andrew Chih-Wei Huang (Brain Sciences, 2023)
Cancer patients regularly suffer from the behavioral symptoms of chemotherapy-induced nausea and vomiting. Particularly, it is involved in Pavlovian conditioning. Lithium chloride (LiCl) was used as the unconditioned stimulus (US) and contingent with the tastant, for example, a saccharin solution (i.e., the conditioned stimulus; CS), resulted in conditioned taste aversion (CTA) to the CS intake. The present study employed an animal model of LiCl-induced CTA to imitate chemotherapy-induced nausea and vomiting symptoms. Recently, the basolateral amygdala (BLA) was shown to mediate LiCl-induced CTA learning; however, which brain mechanisms of the BLA regulate CTA by LiCl remain unknown. The present study was designed to test this issue, and 4% lidocaine or D2 blocker haloperidol were microinjected into BLA between the 0.1% saccharin solution intake and 0.15M LiCl. The results showed lidocaine microinjections into the BLA could attenuate the LiCl-induced CTA. Microinjections of haloperidol blunted the CTA learning by LiCl. Altogether, BLA via the sodium chloride ion channel and D2 receptors control LiCl-induced conditioned saccharin solution intake suppression. The findings can provide some implications and contributions to cancer chemotherapy-induced nausea and vomiting side effects, and will help to develop novel strategies to prevent the side effects of cancer chemotherapy.